2013
DOI: 10.1590/s1984-82502013000400013
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C in prisoners and non-prisoners in Colatina, Espírito Santo, Brazil

Abstract: The aim of the present work was to compare hepatitis C prevalence, genotypes, and risk factors between prisoners and non-prisoners in the city of Colatina, Espírito Santo, Brazil. This cross-sectional study involved approximately 1,600 residents and 730 prisoners, all of whom were living in Colatina. The percentage of individuals who tested positive for anti-HCV was 0.1% (2/1,600) in the non-prisoner group and 1.0% (7/730) in the prisoner group, confirming a higher risk of hepatitis C in the latter group. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The first one used second-generation ELISA and the other, third-generation ELISA. The other studies are from later years, 7 , 10 - 12 , 27 , 32 , 35 , 36 , 40 when it was possible to access second- and third-generation kits. The articles that described the generation or version of the kit and used the third-generation kit are shown in Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first one used second-generation ELISA and the other, third-generation ELISA. The other studies are from later years, 7 , 10 - 12 , 27 , 32 , 35 , 36 , 40 when it was possible to access second- and third-generation kits. The articles that described the generation or version of the kit and used the third-generation kit are shown in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 18 , 32 , 40 The second- and third-generation ELISA tests have a specificity of approximately 99.0%, so the chance of false-positive results is generally considered not significant. Five studies performed confirmatory tests, four of them with in-house molecular testing (presence of virus), and the percentages of confirmed positive cases were 100%, 12 94.5%, 26 91.7%, 36 69.0%, 32 and 55.5% 7 ( Table 1 ). This raises questions about false-positive results in serology and possible difficulties in molecular testing, such as detecting a phase of low viremia or seroconversion, the high cost of supplemental tests for diagnosing HCV infection and the need for adequate laboratory infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…In the non-incarcerated population, the prevalence of HCV-RNA and anti-HCV was 0.1% (2/1600). 11 However, the study conducted in Finland with 88 women and 300 men showed a high prevalence of antibodies against HCV, 52% in the groups. Among females, 71% and males, 43.9%.…”
Section: Descriptive / IV -( N= 195)mentioning
confidence: 94%
“…When separating by sex, Puga (2015) demonstrated in 3,771 prisoners randomly selected in Mato Grosso do Sul (84.6% male and 15.4% female) that anti-HCV seropositivity was different between men (2.7%) and women (0.6%). Regarding to individuals in the city of Colatina, state of Espírito Santo, Falquetto et al [12] found anti-HCV seropositivity in 0.4% among all participants. But, when comparing people inside (730 individuals) and outside…”
Section: Pompilio Mauríciomentioning
confidence: 99%